Effective management of financial resources - Matvieieva, Yana (My University, 2014)
One of the most essential conditions on the way to the stabilization of the socio-economic situation in Ukraine in market conditions is to achieve the effective fimctioning of enterprises. The transforming of the Ukrainian economy to a market causes a number of problems: providing the enterprises by financial resources and transfer the performance responsibility of specific economic and financial indicators to the heads of individual areas.
Keywords: financial resources; socio-economic situation; management; финансовые ресурсы; социально-экономическая ситуация; управление; управління; соціально-економічна ситуація; фінансові ресурси